Analysis of The Impact of Space Application Patterns in Placing the Location of Economic Activities Through the Conversion Mechanism of Raw Land Field Land Conversion - Sukiptiyah Sukiptiyah; Ernan Rustiadi; Akhmad Fauzi; Baba Barus (Journal Research of Social Science, Economics, and Management, 2022)
Conversion of agricultural land into built-up land is a regional economic development mechanism, where to increase Gross Domestic Product can be done by allocating the widest possible pattern of space designation "industry, trade and settlement", the implication is the conversion of agricultural land into built-up land. land (rice fields) increases and rice production facilities decrease so that food fulfillment is constrained, in other words there is a trade off in the use of paddy fields. In an effort to optimize the allocation of space for rice fields, the purpose of this study is to analyze the factors of space allocation in influencing the location of economic activities (industry and housing) in rural areas. Through the mechanism for conversion of paddy fields and the determination of the priority scale for the revision of the designation pattern of paddy fields in the regional spatial plan. This study uses spatial overlay analysis, quantitative calculations, multiple linear regression and spatial analysis of 4 criteria (space allocation, road access, population density and land prices). The research locations are distinguished in rural areas with high and low industrialization and urbanization. Input data using spatial software with overlay techniques including spatial data on administrative boundaries of the sub-district area, paddy land use in 2013 and 2018, road access (tolls, arteries and collectors) in 2018, spatial allocation based on the Regency Spatial Plan, value zone land in 2018 and population density. The results showed that the location of economic activities (industrial and housing) was relatively influenced by the space allocation factor compared to the road access factor. Revision of Spatial Plan is recommended in rural areas with high rice field conversion potential in rural areas with high industrialization and urbanization.